TESTING MITOCHONDRIAL CAPTURE AND DEEP COALESCENCE IN AMAZONIAN CICHLID FISHES (CICHLIDAE: CICHLA). (1st January 2014) - Willis, Stuart C.; Farias, Izeni P.; Ortí, Guillermo
Abstract: Hybridization and introgression have important consequences in evolution, such as increasing the genetic diversity and adaptive potential of a species. One of their most conspicuous footprints is discordance among gene trees or between genes and phenotypes. However, most studies that report introgression fail to disprove the null hypothesis that genetic incongruence may result from stochastic sorting of ancestral allelic polymorphisms. In the case of ancient introgression, these two processes may be especially difficult to distinguish topologically, but they make different predictions about the patterns of coalescence among loci. Here we apply three methods, molecular dating, multispecies coalescent models, and gene tree simulation under coalescence, to compare these two hypotheses that explain the polyphyletic mtDNA of the butterfly peacock bass, Cichla orinocensis . In comparison with a species tree based on 20 unlinked nuclear loci, we determined that mtDNA divergences were too recent to be explained by ancestral polymorphism. Similarly, coalescent species tree branches were significantly shorter when putative introgressed mtDNA was incorporated, and simulations showed the mtDNA topology to be unlikely under lineage sorting only. We conclude that introgression approximately 1.5 million years ago resulted in capture by C. orinocensis of an mtDNA lineage ancestral to the modern subspecies C. oc. monoculus .